2020
DOI: 10.3390/ani10091691
|View full text |Cite
|
Sign up to set email alerts
|

E4 Transcription Factor 1 (E4F1) Regulates Sertoli Cell Proliferation and Fertility in Mice

Abstract: In the mammalian testes, Sertoli cells are the only somatic cells in the seminiferous tubules that provide structural, nutritional and regulatory support for developing spermatogenic cells. Sertoli cells only proliferate during the fetal and neonatal periods and enter a quiescent state after puberty. Functional evidences suggest that the size of Sertoli cell population determines sperm production and fertility. However, factors that direct Sertoli cell proliferation and maturation are not fully understood. Tra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 58 publications
0
7
0
Order By: Relevance
“…As a multifunctional transcription factor, E4F1 plays an essential role in cell fate decisions and interacts with Retinoblastoma protein (pRB), a regulator of Sertoli cells [34]. Due to the mortality of the preimplantation embryos in E4F1 knockout mice, the E4F1 is thought as a necessary gene for early embryonic development [32].…”
Section: E4f1mentioning
confidence: 99%
“…As a multifunctional transcription factor, E4F1 plays an essential role in cell fate decisions and interacts with Retinoblastoma protein (pRB), a regulator of Sertoli cells [34]. Due to the mortality of the preimplantation embryos in E4F1 knockout mice, the E4F1 is thought as a necessary gene for early embryonic development [32].…”
Section: E4f1mentioning
confidence: 99%
“…A recent study by Rajak et al (2016b) showed that “good” bulls had a significantly higher (25%) proportion of Sertoli cells in testicular cytology compared to “poor” bulls (11%). Sertoli cells are capable of supporting only a finite number of germ cells; the final number of Sertoli cells in a given male sets the upper limit for testicular sperm production ( Waqas et al, 2019 ) and determines the level of male fertility ( Yan et al, 2020 ). A high number of Sertoli cells per spermatogenic cell would be expected to provide sufficient support and nourishment for successful progression of spermatogenesis and for production of good-quality spermatozoa.…”
Section: Compounding Factors For Infertility/sub-fertility In Crossbred Bullsmentioning
confidence: 99%
“…E4f1 knockout leads to the exhaustion of the epidermal stem cell pool in skin [ 22 ]; however, its deficiency does not affect the stem cell compartment but instead causes the depletion of multipotent progenitors in the hematopoietic system [ 20 ]. Conditional deletion of E4f1 in Sertoli cells did not cause severe defects in spermatogenesis, indicating its intriguing roles in different tissues [ 26 ]. Because of its essential roles in metabolism, deciphering the function of E4F1 in spermatogenic cells will facilitate the understanding of the metabolic control of SSC fate decisions.…”
Section: Introductionmentioning
confidence: 99%